Analysis Of Lead (Pb) Heavy Metal Content In Smoking Farmers: Analisis Kandungan Logam Berat Timbal (Pb) Pada Petani Perokok - Tamala, Desy; Hanum, Galuh Ratmana (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
Farmers in the village of kedungrejo jombang in carrying out their activities some of them have a smoking habit where in cigarettes there are some heavy metal content such as lead (Pb). Lead (Pb) is a heavy metal that is toxic to human health. Lead can cause interference and damage to the kidney function system. The purpose of the study was to determine the relationship between lead heavy metals in the urine of actve and passive smokers in kedungrejo village. This research used the Atomic Absorption Spectrophotometer (AAS) method with 20 farmer urine samples. The results showed that lead heavy metal levels were below the threshold value of 0,15 mg/l. The results of Pearson correlation obtained p value = 0,021 ; r = 0,510. It can be concluded that there is a moderate relationship between heavy metals and urine of active and passive smokers of farmers.